The Influence of Transactional Leadership Style and Organizational Commitment on Organizational Citizenship Behavior in Pt. Merapi Utama Pharma Pekanbaru Branch - Haryoto, Cecep Yoto (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to determine the influence of transactional leadership style and organizational commitment on organizational citizenship behavior at PT. Merapi Utama Pharma Pekanbaru Branch. Data collection was carried out by distributing questionnaires with a Likert scale. The results of this research show that transactional leadership has a positive and significant effect on organizational citizenship behavior, organizational commitment has a positive but not significant effect on organizational citizenship behavior, transactional leadership and organizational commitment have a positive and significant effect on organizational citizenship behavior.